Application of Fuzzy Service Quality Method in Student Satisfaction Analysis of School Service Quality at SMAN 1 Simanindo, Samosir Regency: Penerapan Metode Fuzzy Service Quality Dalam Analisis Kepuasan Siswa Terhadap Kualitas Pelayanan Sekolah SMAN 1 Simanindo Kabupaten Samosir - Siahaan, Irfan Efendi; Marbun, James Piter (Journal of Mathematics Technology and Education, 2022)
To improve the quality of service, it is necessary to know the extent to which thelevel of consumer assessment of service quality, whether the service received is in accordancewith consumer expectations or not. This research was conducted to determine student satisfaction with the service quality of SMAN 1 Simanindo School. The method used in this studyis the Fuzzy Service Quality method which aims to determine the gap that occurs between theservices received and student expectations. The results of data processing indicate that theattribute that is the main concern to be prioritized by the school so that improvements can bemade is the completeness of extracurricular support with a gap (-15.370). Based on the valueof the gap per dimension, the dimension that has the largest gap value is the dimension thatneeds to be prioritized by the school for improvement. The dimension that has the largest gapvalue is the physical dimension (tangiable) with a gap value of -12.98. Based on the Cartesiandiagram, the attributes that require priority treatment from the school are the completeness ofbooks and reference sources in the library and the school’s ability to produce quality alumni.The attributes of the question are located in quadrant I. Based on the Fuzzy Service Qualityanalysis, the overall attributes have a negative gap value. This shows that the quality of service provided by the school is unsatisfactory and still in dire need of improvement.